Electrochemical Profile of LiTi2(PO4)3 and NaTi2(PO4)3 in Lithium, Sodium or Mixed Ion Aqueous Solutions. Issue 6 (1st January 2016) - Chen, Long; Liu, Jingyuan; Guo, Zhaowei; Wang, Yonggang; Wang, Congxiao; Xia, Yongyao
Abstract : Carbon-coated LiTi2 (PO4 )3 and NaTi2 (PO4 )3 were prepared using the sol-gel method, followed by solid-state reaction and thermal decomposition vapor deposition process. The electrochemical profile of both compounds were examined in three different aqueous electrolytes, including 1 M Li2 SO4, 1 M Na2 SO4 and 1 M Li2 SO4 /Na2 SO4 mixed solutions (1:1 in the volume ratio). Both Li and Na ions can successfully inserted into these NASCION materials, and the two materials deliver a similar higher discharge potential in the Li2 SO4 solution (−0.76 V vs. Ag/AgCl) compared to that in the Na2 SO4 solution (−0.8 V vs. Ag/AgCl) after several charge/discharge cycles. The XRD analysis demonstrate that LiTi2 (PO4 )3 is converted to NaTi2 (PO4 )3 in the Na2 SO4 and mixed solutions, and NaTi2 (PO4 )3 was transformed to LiTi2 (PO4 )3 in the Li2 SO4 solution after cycling. It suggests that the Li or Na ions in the M1 sites of the NASCION materials are replaced by the ions from the electrolyte, but Na ions prefer to occupy the M1 sites compared with Li ions.